Keterbatasan Anggaran Prodeo PHI terhadap Pelaksanaan Kekuasaan Kehakiman PN Banjarmasin Perspektif HTN - Ahmad Irfansyah Rosyadi; Salsabila Syifana Alkamila; Khairun Nisa; Hapip Udin; Fadhil Rozin Asyam (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
Prodeo legal aid is one of the ways in which the state fulfils its responsibility to guarantee access to justice for economically disadvantaged members of the public. However, its implementation still faces challenges, particularly budgetary constraints, meaning that not all applications for prodeo legal aid can be processed. This issue arises in Industrial Relations Court (PHI) cases at the Banjarmasin District Court. This study aims to examine the implementation of prodeo services in PHI cases and to analyse these budgetary constraints from a constitutional law perspective. The methodology employed is a normative legal approach with an empirical focus, utilising a review of legislation, interviews, observations, and a literature review. The research findings indicate that prodeo is a service for litigation at no cost, funded by the state through the State Budget Allocation (DIPA). In 2025, a budget of Rp. 33,728,000 was only sufficient to handle 13 cases, meaning the service depends on the availability of funds. This situation reflects a gap between the constitutional guarantee of access to justice and practice on the ground. Therefore, improvements are needed in budget planning, allocation, and management, as well as the strengthening of the role of Legal Aid Posts and Legal Aid Institutions to enhance access to justice for the underprivileged.